33. ASSOCIATION OF FOXP3+ TUMOUR INFILTRATING LYMPHOCYTE DENSITY IN PRIMARY MELANOMA WITH BRAF AND NRAS MUTATION STATUS. (February 2015) - Leslie, Connull; Bowyer, Samantha; White, Alison; Grieu-Iacopetta, Fabienne; Iacopetta, Barry; Amanuel, Benhur; Millward, Michael
Abstract : Background: Activating mutations in codon 600 of the BRAF gene are found in 40–60% of melanomas and mutation identification has provided a drugable target. Tumour immune response has been shown to influence melanoma growth and metastasis and studies show that tumour infiltrating lymphocytes (TILs) present in primary excision biopsies correlate with patient outcome. Regulatory T cells are a subpopulation of TILs known to down-regulate immune-mediated inflammation which express transcription factor forkhead box protein 3 (FOXP3). We assessed the density of FOXP3+ cells in primary melanoma samples of a cohort of patients with subsequent metastasis. The density of FOXP3 cells was compared to BRAF and NRAS mutational status as well as treatment response in those treated with BRAF inhibitor. Methodology: Immuohistochemical staining for CD20, CD3, CD4, CD8, CD56 and FOXP3 and BRAF and NRAS mutational status by PCR was performed on primary melanoma tissue samples in 81 cases. Image analysis software (Aperio) was used to count the number of positive cells by applying a nuclear counting algorithm. Results: Lymphocytes positive for FOXP3 were present in highly variable densities. The intratumoural density ranged from 0.6 to 638 (mean 78.8) cells per mm 2 . The peritumoural density ranged from 5.0 to 842 (mean 257.9) cells per mm 2 . BRAF but not NRAS mutation was associated with higher intratumoral FOP3+ counts. Conclusion: Primary melanomas with a BRAF mutation had a significantly higher intratumoural density of FOXP3+ cells than melanomas wildtype for BRAF mutation ( p = 0.0258). There was no relationship between FOXP3 count and NRAS mutation or response to BRAF inhibitor therapy. There was a higher density of FOXP3+ cells in thinner melanomas in this group with subsequent metastatic disease.